Phase Preserving Tone Mapping of Non-Photographic High Dynamic Range Images - Kovesi, P. (2012 International Conference on Digital Image Computing: Techniques and Applications, 2012)
Non-photographic images having a high dynamic range, such as aeromagnetic images, are difficult to present in a manner that facilitates interpretation. Standard photographic high dynamic range (HDR) algorithms may be unsuitable, or inapplicable to such data. We present a method that compresses the dynamic range of an image while preserving local features. It makes no assumptions about the formation of the image, the feature types it contains, or its range of values. Thus, unlike algorithms designed for photographic images, this algorithm can be applied to a wide range of scientific images. The method is based on extracting local phase and amplitude values across the image using monogenic filters. The dynamic range of the image can then be reduced by applying a range reducing function to the amplitude values, for example taking the logarithm, and then reconstructing the image using the original phase values. An important attribute of this approach is that the local phase information is preserved, this is important for the human visual system in interpreting the image. The result is an image that retains the fidelity of its features within a greatly reduced dynamic range. An additional advantage of the method is that the range of spatial frequencies that are used to reconstruct the image can be chosen via high-pass filtering to control the scale of analysis.